Implementation of the release of TNI AD occupation land/building assets that cause disputes in the Kodam IV/Diponegoro area - Diki Kurniawan (Annals of Justice and Humanity, 2023)
Purpose: Since the beginning of the independence of the Republic of Indonesia, the interests of regional defense and security have been the main focus. This resulted in many lands and buildings being controlled by the Indonesian National Army (TNI) as part of the occupation in the interest of state security. Although the Basic Agrarian Law (UUPA) of 1960 has abolished the basis of colonial regulations related to land and buildings, ownership of land/buildings occupied by the TNI is still a legal debate. The case of Wisma Kaliurang in Yogyakarta shows the complexity of this conflict, where the legal owner, in this case Samuel Soegito's heirs, has paid compensation to the Indonesian Army and obtained a certificate for the land/building. However, Kodam IV/Diponegoro still claims ownership of the assets of the Indonesian Army Occupation. Research methodology: In resolving this kind of conflict, it is important to ensure that the ownership status of the original owner needs to be recognized and respected, while also taking into account the defense and security needs of the Indonesian state.